2019
DOI: 10.17220/mojet.2019.01.006
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Digital Concept Maps in Online Learning Environments on Students’ Success and Disorientation

Abstract: Concept and knowledge maps are used often in learning process as two dimensional learning materials. These maps are important in comprehending concepts of a subject and relationships between these concepts. Nowadays, concept maps can be used beyond student drawings as digital navigation tools in real life. The aim of this study is to investigate the impact of the use of digital concept maps as navigation tools in online learning environments on student success and disorientation. There are two subdimensions of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 0 publications
0
2
0
2
Order By: Relevance
“…Besides, the establishment of the concept map also improves students' information literacy because before they create the concept map, they find information from relevant sources. Also, the creation of concept map aids students in better understanding a particular concept and the correlation among concepts [40]. The previous study also states that the establishment of a concept map involves understanding a text, analysis, information synthesis, and information representation, improving students' information literacy [41].…”
Section: Resultsmentioning
confidence: 96%
“…Besides, the establishment of the concept map also improves students' information literacy because before they create the concept map, they find information from relevant sources. Also, the creation of concept map aids students in better understanding a particular concept and the correlation among concepts [40]. The previous study also states that the establishment of a concept map involves understanding a text, analysis, information synthesis, and information representation, improving students' information literacy [41].…”
Section: Resultsmentioning
confidence: 96%
“…in learning environments (Novak, 2009). When the literature is reviewed, numerous studies are found that its positive educational outputs on the use of paper-based mind maps (PBMMs) in several field such as foreign language (Gomleksiz & Yetkiner, 2012), science (Balim, 2013;Keskinkilic-Yumusak, 2013;Hidayati, Zubaidah, Suarsini, & Praherdhiono, 2020), music (Coban & Selcuk-Tokatli, 2017), social sciences (Karadeniz, Tangulu, & Faiz, 2013), maths (Ozdemir, Alaybeyoglu & Filiz-Balbal, 2017), instructional technologies (Aydogdu & Guyer, 2019). On the other hand, students as today's digital natives often use and prefer digital media, which have been effective in the development of their mind maps and the creation of "interactive mind maps (iMindMap)" in a technological form (Willis & Miertschin, 2006;Zipp, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Hasil yang diperoleh dari penelitian Aydogdu & Guyer bahwa selama pengujian media, pemetaan konsep memberikan penyederhanaan materi yang kompleks. Kekurangannya adalah siswa akan mengalami disorientasi materi jika peta konsep yang dikembangkan tidak sederhana [5].…”
unclassified